Photocatalytic trifluoromethoxylation of arenes and heteroarenes in continuous-flow - Nyuchev, Alexander V.; Wan, Ting; Cendón, Borja; Sambiagio, Carlo; Struijs, Job J. C.; Ho, Michelle; Gulías, Moisés; Wang, Ying; Noël, Timothy (Beilstein Journal of Organic Chemistry, 2020)
The first example of photocatalytic trifluoromethoxylation of arenes and heteroarenes under continuous-flow conditions is described. Application of continuous-flow microreactor technology allowed to reduce the residence time up to 16 times in comparison to the batch procedure, while achieving similar or higher yields. In addition, the use of inorganic bases was demonstrated to increase the reaction yield under batch conditions.
Keywords: C–H functionalization; continuous-flow; organic synthesis; photoredox catalysis; trifluoromethoxylation